Evaluating the scope and impact of pre-diagnostic manipulative therapy in children and adolescents with osteosarcoma: A retrospective study in Uganda - Richard Nyeko; Fadhil Geriga; Racheal Angom; Joyce Balagadde Kambugu; Jaques van Heerden (PLoS ONE, 2025)
Background Pre-diagnosis manipulative therapies in patients diagnosed with osteosarcoma can compromise patients’ outcomes. Limited literature exists on the pre-diagnosis non-oncological management of osteosarcoma, especially in resource-limited settings. We described and characterized the practice of pre-diagnosis manipulative therapy at the reference cancer treatment center in Uganda as a first step to improving the quality along the osteosarcoma treatment pathway. Methods We reviewed the demographic and clinical characteristics, pre-referral management, and outcome of children under 18 years treated for osteosarcoma at the Uganda Cancer Institute between January 2016 and December 2020. Data on pre-diagnosis management were extracted, as well as clinical and disease characteristics and outcome. Descriptive statistics and Kaplan-Meier survival analysis were used. Results Nineteen (25.7%) of the 74 children with osteosarcoma in the current study had undergone prior manipulative therapy. The main forms of manipulative therapy were local therapeutic cuttings with the application of local herbs in 6 (31.5%) patients, massaging in 5 (26.3%), attempted incision and drainage in 4 (21.1%), and treatment as a local infection (osteomyelitis or arthritis) in 4 (21.2%). The majority, 15 (78.9%), of the patients who had manipulative therapy were males (X² = 5.73; p = 0.031). Children who underwent manipulative therapy were referred after a median of 45 days (range 11–139) compared to their counterparts, who were referred after a median of 28 days (range 1–147) (p = 0.012). Patients with manipulative therapy had a metastatic rate of 77.8%, while the rate was 60.4% for those who did not have manipulative therapy. The serum lactate dehydrogenase level was higher in patients who had manipulative therapy compared to those who did not have manipulative therapy (X2 = 3.98; p = 0.046). The median survival was 1.0 year (95% CI 0.8–1.3) for patients who underwent prior manipulative therapy and 1.8 years (95% CI 1.4–2.2) for those who did not report any form of manipulative therapy (p = 0.961). Conclusion Pre-diagnosis manipulative therapies lead to poorer outcomes in patients diagnosed with osteosarcoma, underscoring the need for bridging the quality gap in the osteosarcoma treatment pathway. This should include sensitization of the community and healthcare provider’s, strengthening patient referral pathways, and improved accessibility to cancer treatment centers.